What role for deliberative minipublics in sustainability transformations? An emerging topic for sustainability science - Tim M. Daw; Simon West; Andrea Downing; Naghmeh Nasiritousi; Marina Lindell; Thomas Hahn; Mikael Karlsson; Tord Snäll; Daniel Lindvall (Sustainability Science, 2026)
Democracies struggle to translate sustainability science, and public concern into sufficiently transformative actions. Ongoing polarization, politicization and disinformation extenuate this challenge. Some scholars suggest that deliberative democratic innovations can help to bridge science, public understanding and will formation, and policy implementation in the face of vested interests. In light of these challenges, we introduce deliberative mini-publics (DMPs), and why they are of interest to sustainability scientists. DMPs are distinguished from participatory methods more familiar to sustainability scientists by their random and stratified selection of ‘ordinary citizens’. An emphasis is also placed on facilitated deliberation, access to information and learning. Evidence shows that the particular conditions of DMPs can support more deliberative and informed reasoning and offer a considered public voice for decision-makers, fellow citizens and sustainability scientists. However, evidence of their wider effect on society and sustainability is mixed and warrants further examination. We draw on examples from emerging research and experience of DMPs to conceptualize three broad mechanisms for how they could potentially enhance the relationship between sustainability science, publics and politics. These differ based on whether they are primarily aiming to (1) inform policy-makers, (2) support public discourse, or (3) enhance transdisciplinary science. We also explore whether DMPs can challenge unsustainable systems and contribute to transformation through visioning, strategizing transitions, and scrutinizing the decisions of public agencies. We encourage experimentation and critical research on DMPs for sustainability transformations to test and better understand their potential.